Use of Cluster Analysis for Development of Star Tracker Mass Statistical Model. (2017) - Kucherov, Alexander; Kurenkov, Vladimir
Abstract: This article deals with the problem of developing the statistical model of spacecraft star trackers mass. Cluster analysis is involved in order to obtain adequate results. Some up-to-date star trackers types are examined and the regression model for a star tracker mass dependent on their main parameters is put forward. The model gives an opportunity to estimate star tracker mass at the initial stages of spacecraft designing.